Do Obese Women Need Higher Dosages of Misoprostol for Labor Induction? [6A]. (May 2016) - Sherwin, Alyse; Cioffi, Joseph; Calixte, Rose; Kinzler, Wendy L.; Vintzileos, Anthony M.
Abstract : INTRODUCTION: To determine the association between maternal BMI and time to delivery in women receiving misoprostol for labor induction (IOL). METHODS: This is a retrospective cohort study of women undergoing IOL with intravaginal misoprostol from 1/2013–2/2015. Women admitted for IOL with singleton, term, cephalic gestations were identified through a database. Maternal demographics, obstetrical variables, and admission BMIs were collected. Time to delivery (vaginal and cesarean) from the initial misoprostol dose was primary outcome. Groups were made based on maternal BMI and misoprostol dose (25 mcg vs 50 mcg). Time to delivery was compared among BMI categories stratified for misoprostol dose using two-sample t test, Wilcoxon rank sum test, and exact chi-square test. A P value less than 0.05 was considered significant. Kaplan Meyer survival and time to event curves were created. RESULTS: 483 patients were included. Mean gestational age was 39.2±1.6 wks, median parity was 0 (range 0–1), and maternal age was 30.5±6.1. Misoprostol 25 mcg was most commonly used (n=290, 60%). Vaginal delivery was achieved in 79% (n=382). More than 90% (n=435) of the women had BMIs greater than 30. Time to delivery was significantly longer with BMIs greater than 30 when misoprostol 25 mcg was used compared with 50 mcg. For BMIs greater than or equal to 40, time to delivery was six hours longer regardless of dose. CONCLUSION: There is an association between maternal BMI and initial misoprostol dosage on time to delivery. Admission BMI should be taken into consideration when dosing misoprostol for IOL.